2009
DOI: 10.1121/1.3050256
|View full text |Cite
|
Sign up to set email alerts
|

Language experience and consonantal context effects on perceptual assimilation of French vowels by American-English learners of French

Abstract: Recent research has called for an examination of perceptual assimilation patterns in second-language speech learning. This study examined the effects of language learning and consonantal context on perceptual assimilation of Parisian French ͑PF͒ front rounded vowels /y/ and /oe/ by American English ͑AE͒ learners of French. AE listeners differing in their French language experience ͑no experience, formal instruction, formal-plus-immersion experience͒ performed an assimilation task involving PF /y, oe, u, o, i, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 28 publications
(24 reference statements)
7
93
0
1
Order By: Relevance
“…Results of this study contribute to previous studies showing that the perceived similarity of L2 sounds to the L1 categories does not occur in a context-independent manner (e.g., Levy, 2009;Strange, Akahane-Yamada, Kubo, Trent, & Nishi, 2001). Even in the shared L2 sounds where each of them was classified as the sounds represented with the same IPA symbols, the degree of the perceived similarities in each pair is affected by the vowel context and language experience.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Results of this study contribute to previous studies showing that the perceived similarity of L2 sounds to the L1 categories does not occur in a context-independent manner (e.g., Levy, 2009;Strange, Akahane-Yamada, Kubo, Trent, & Nishi, 2001). Even in the shared L2 sounds where each of them was classified as the sounds represented with the same IPA symbols, the degree of the perceived similarities in each pair is affected by the vowel context and language experience.…”
Section: Resultssupporting
confidence: 61%
“…Their findings showed that L2 learners assimilated the non-native sounds to their closest L1 categories. In addition, the perceived similarity between L1 and L2 sounds is context-dependent as shown by many studies For example, Levy (2009) examined the effects of L2 experience and consonantal context on the perceptual assimilation of Parisian French (PF) /y/ and /oe/ by American English learners. The listeners were divided into three groups: no experience (NoExp), formal instruction (ModExp) and formal-plus-immersion experience (HiExp).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, they may have simply been drawing upon vowel tokens that were already in their repertoire: particularly fronted versions of English /u/. It has been proposed that due to the fact that American English /u/, which is already relatively front on average, is further fronted in the context of alveolars, the front vowel /y/ may not actually constitute a "new" vowel for English-speaking L2 learners, but instead a "similar" vowel, at least in the context of alveolars (Strange et al, 2007;Levy, 2009;Levy and Law, 2010). Documented perceptual assimilation patterns in which English speakers identify German and French /y/ as closest to English /u/ (e.g.…”
Section: B "New" Vs "Similar" Categoriesmentioning
confidence: 99%
“…The 240 isolated vowels were extracted from the 20 speakers' first production of /s/-vowel-/s/ words reported in Adank et al (2004). We chose to present participants with isolated vowels to avoid the effect of consonantal context on perceptual assimilation patterns, which has been found in many recent studies (for a review, see Levy, 2009). Figure 1 shows the average F1 and F2 values for the female and male Peruvian Spanish vowel productions reported in Chládková et al (unpublished) and the average F1 and F2 values of the Dutch stimuli.…”
Section: Stimulimentioning
confidence: 99%